An internationalization strategy for a US medical diagnostic firm - Smith, Stephen (2020)
This paper aims to help an American Medical diagnostic firm internationalize further through the use of International Market Selection techniques. The research consisted of interviewing the Director of Operations and a high up anonymous source of the company, as well as using secondary data. Based on interview data, existing literature, as well as secondary data, this paper ranked countries based on market potential and clustered countries based on macro similarities. A CAGE framework was utilized for an in depth analysis of the two top scoring markets. The research found that the most promising market for the company to enter was Australia and found two similar clusters that could potentially be utilized for further expansion. This paper concludes by calling for more research into the countries of those cluster to really analyze the best potential market for the next expansion.